EDUKASI PROTOKOL KESEHATAN DI MASA PANDEMI COVID - 19 PADA WARGA DK. BERDUG KULON RT 01 RW 11, SIDOMULYO, AMPEL, BOYOLALI - VEGI LESTARI; ADHIPUTRO PANGARSO WICAKSONO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The COVID-19 pandemic is still the biggest outbreak in our country. Various ways have been taken by the government to overcome this outbreak, but they have not succeeded. In fact, if the public has self-awareness about the dangers of the Covid-19 virus, and this is accompanied by community discipline in implementing the health protocols that have been established by the government, this can suppress the growth of the Covid-19 virus in Indonesia. Covid-19 has succeeded in changing the habits that we do every day at home, at school, at work, on the road, and anywhere else. As is well known, Covid-19 is a disease caused by the Corona Virus, a very small creature measuring about 125 nanometers but can cause death. Symptoms of Covid-19 are characterized by the appearance of cough, cold, flu, fever, respiratory problems, but some have no symptoms, and in severe conditions they can cause respiratory failure and lead to death. Transmission through coughing or sneezing droplets. In this year's Real Work Lecture (KKN) activity which was held at Dukuh Kulon Rt 01 Rw 11 Sidomulyo, Ampel Subdistrict, Boyolali Regency, has a joint program against Covid 19 towards an independent village and has the potential to get used to always wearing masks and implementing the 5M health protocol ( wearing a mask, washing hands with soap and running water, maintaining distance, staying away from crowds, limiting mobilization and interaction)